The Last Ottomans - Featherstone, K. author. aut Link
XXIV, 354 p.
Keywords: A new study of the international and local politics surrounding the Muslim minority of Western Thrace (Greece) in the 1940s, based on previously unseen archival material. Addresses the minority's complex identity, its relations with other communities in the area, the international diplomacy of WWII and strategic considerations of the Cold War.